2023
DOI: 10.1093/ageing/afac326
|View full text |Cite
|
Sign up to set email alerts
|

The effect of thyroid hormone therapy on muscle function, strength and mass in older adults with subclinical hypothyroidism—an ancillary study within two randomized placebo controlled trials

Abstract: Background loss of skeletal muscle function, strength and mass is common in older adults, with important socioeconomic impacts. Subclinical hypothyroidism is common with increasing age and has been associated with reduced muscle strength. Yet, no randomized placebo-controlled trial (RCT) has investigated whether treatment of subclinical hypothyroidism affects muscle function and mass. Methods this is an ancillary study within… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Skeletal muscle is a primary target of TH signaling, influencing structural and metabolic properties, thus several studies have addressed the role of TH in muscle health (33) There (2022) on 267 older adults with persistent subclinical hypothyroidism revealed that LT4 treatment did not significantly affect gait speed, handgrip strength, or annual muscle mass change when compared to a placebo (35).…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal muscle is a primary target of TH signaling, influencing structural and metabolic properties, thus several studies have addressed the role of TH in muscle health (33) There (2022) on 267 older adults with persistent subclinical hypothyroidism revealed that LT4 treatment did not significantly affect gait speed, handgrip strength, or annual muscle mass change when compared to a placebo (35).…”
Section: Discussionmentioning
confidence: 99%
“…The mean age was 77.5 years, and 48.3% were women. 30 Compared to the placebo, participants in the L-T4 group had similar gait speed at the final visit (adjusted between-group mean difference, similar handgrip strength at 1 year, and similar yearly change in muscle mass). These findings suggest that the ancillary analysis of two RCTs and treatment of SCH did not affect muscle function, strength, and mass in individuals 65 years and older.…”
Section: Skeletal Healthmentioning
confidence: 91%
“…Three studies on the subject were published recently. [28][29][30] The impact of L-T4 therapy for SCH on appendicular bone geometry and volumetric density was studied in a nested study within the TRUST trial by Büchi et al 28 assessing the effect of L-T4 therapy on bone geometry as measured by peripheral quantitative computed tomography. In the TRUST trial, community-dwelling adults aged 65 years with SCH were randomized to L-T4 with dose titration versus placebo with mock titration.…”
Section: Skeletal Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Restoration of normal albumin concentrations, associated with dietary supplementation of BCAA, is correlated with a reduction of fat accumulation in skeletal muscle, preservation of muscle mass and improved glucose sensitivity in patients with liver cirrhosis [ 72 ]. Interestingly, an ancillary analysis of two RCTs, treatment of subclinical hypothyroidism had no significant effect on function, strength and muscle mass in subjects aged 65 years and older [ 73 ]. Compared to placebo, testosterone replacement (7.5 g testosterone gel at 1% per day) in elder men with low to moderate–normal testosterone levels for 3 years was associated with modest but significantly greater improvements in muscle mass [ 74 ].…”
Section: Therapeutical Approachesmentioning
confidence: 99%